WEB ANTARMUKA PENDUKUNG VISUALISASI SORTING (Information Technology and Telematics, 2015)
Abstract The era of globalization makes sorting the data is one of the most important parts of the computer world. The data sequencedby specific category caneasily searchable, corrected, deleted, inserted or combined, can check the lost data. Methods of exchange sort and bubble sort are simple methods but a way of teaching the existing sorting is difficult to reason. This happens because the existing squencing visualization program can not display the step details of each data exchange although the time required in the process of sorting and the existing squencing visualization program are not web-based visualization program and use Indonesian. Made web-based visualization exchange sort and bubble sort can help the problem above. Subjects of this study iscreate web-based visualization that can describe the methods of exchange sort and bubble sort. The type of data that can be sorted are numbers (0-9), letters anda combination both of them. The maximum of input is 15 data which the input is directly by the web user. The program uses HTML 5 canvas with Javascript as interpreter and processed by software Notepad ++. With theweb-based visualization of methods exchange sort and bubble sort so the process of the methods becomes easy to understand. Use of the HTML programming language as the implementation of that visualization can be clearly in doing every step of the algorithm. Javascript makes web interface more interactive by giving the facility to include in the form of a variety of options and can control the visualization that is being executed. The use of HTML 5 canvas element makes displacement of any exchange in the sorting process becomes more clearly and interesting. Keyword :Visualization, Sorting, Bubble Sort, Exchange Sort, Canvas